2009
DOI: 10.1136/hrt.2008.164657
|View full text |Cite
|
Sign up to set email alerts
|

"So you think I'll survive?": a qualitative study about doctor-patient dialogues preceding high-risk cardiac surgery or intervention

Abstract: Objective: To explore doctor-patient interactions and decision-making processes before high-risk cardiac surgery or intervention with special attention to existential challenges. Design, setting and participants: We conducted a qualitative study with data drawn from doctor-patient dialogues preceding high-risk procedures. The study setting was the cardiac department of a university hospital with 24-hour emergency service. We recruited a purposive sample of 10 patients and eight doctors. The patients were categ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
35
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(35 citation statements)
references
References 41 publications
(27 reference statements)
0
35
0
Order By: Relevance
“…Though existential issues need not result in distress (Blinderman & Cherny, 2005), it is important for health care providers to be able to identify and address these aspects of patients' experiences due to potential negative consequences like anxiety, depression, and loss of will to live (Chochinov et al, 2005; McCoubrie & Davies, 2006) as well as predicting positive outcomes (Vollman, LaMontagne, & Wallston, 2009) and understanding complex decision-making processes (Schaufel, Nordrehaug, & Malterud, 2009). Existential distress is “the distressed state of an individual confronting their own mortality, and arising from the consequent feelings of powerlessness, futility, meaninglessness, disappointment, remorse, death anxiety and the disruption of personal identity; the experience of life without meaning” (Kissane, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Though existential issues need not result in distress (Blinderman & Cherny, 2005), it is important for health care providers to be able to identify and address these aspects of patients' experiences due to potential negative consequences like anxiety, depression, and loss of will to live (Chochinov et al, 2005; McCoubrie & Davies, 2006) as well as predicting positive outcomes (Vollman, LaMontagne, & Wallston, 2009) and understanding complex decision-making processes (Schaufel, Nordrehaug, & Malterud, 2009). Existential distress is “the distressed state of an individual confronting their own mortality, and arising from the consequent feelings of powerlessness, futility, meaninglessness, disappointment, remorse, death anxiety and the disruption of personal identity; the experience of life without meaning” (Kissane, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…These findings highlight a need for future communication skills training for physicians in the ICU. Effective decision-making between families and physicians in the ICU depends on alignment of family and team understanding of prognosis, and ability to communicate in the setting of high emotional and existential stress [36]. Sharing prognostic information and checking family understanding are therefore essential communication skills for a physician in the ICU.…”
Section: Empathic Communication: Identifying and Responding To Emotionmentioning
confidence: 99%
“…It has also been suggested that when handling uncertainty, doctors are focused on imparting complex information about risk, while for patients, the manner of information provision may serve to establish doctors' trustworthiness. 110 Positive encounters with staff included those who had made an effort to answer questions fully and provide explanations at an appropriate level. Nurses were usually thought to have more time to talk to patients, and to be better communicators, than surgeons or cardiac consultants.…”
Section: Ha10 Male MI In 2003 Aged 63 Yearsmentioning
confidence: 99%